Retinopathy as an initial sign of hereditary immunological diseases: report of six families and challenges in eye clinic - Wang, Yingwei; Jiang, Yi; Wang, Junwen; Li, Shiqiang; Jia, Xiaoyun; Xiao, Xueshan; Sun, Wenmin; Wang, Panfeng; Zhang, Qingjiong (Frontiers in Immunology, 2023)
Retinal degenerative or inflammatory changes may occur with hereditary immunological disorders (HID) due to variants in about 20 genes. This study aimed to investigate if such retinopathy may present as an initial sign of immunological disorders in eye clinic. Variants in the 20 genes were selected from in-house exome sequencing data from 10530 individuals with different eye conditions. Potential pathogenic variants were assessed by multistep bioinformatic analysis. Pathogenic variants were defined according to ACMG/AMP criteria and confirmed by Sanger sequencing, co-segregation analysis, and consistence with related phenotypes. Ocular clinical data were thoroughly reviewed, especially fundus performance. A total of seven pathogenic variants in four of the 20 genes were detected in six probands from six families, including three with hemizygous nonsense variants p.(Q308*), p.(Q416*), and p.(R550*) in MSN, one with homozygous nonsense variants p.(R257*) in AIRE, one with compound heterozygous nonsense variants p.(R176*) and p.(T902*) in LAMB2, and one with a known c.1222T>C (p.W408R) heterozygous variant in CBL. Ocular presentation, as their initial signs of the diseases, was mainly retinopathy mimicking other forms of hereditary retinal degeneration, including exudative vitreoretinopathy in the three patients with MSN variants or tapetoretinal degeneration in the other three patients. Neither extraocular symptoms nor extraocular manifestation were recorded at the time of visit to our eye clinic. However, of the 19 families in the literature with retinopathy caused by variants in these four genes, only one family with an AIRE homozygous variant had retinopathy as an initial symptom, while the other 18 families had systemic abnormalities that preceded retinopathy. This study for the first time identified six unrelated patients with retinopathy as their initial and only presenting sign of HID, contrary to the previous reports where retinopathy was the accompany sign of systemic HID. Recognizing such phenotype of HID may facilitate the clinical care of these patients. Following-up visit on such patients and additional studies are expected to validate and confirm our findings.